Kinematic Analysis During Straight Line Free Swimming in Horses: Part 1 - Forelimbs - Santosuosso, Emma; Leguillette, Renaud; Vinardell, Tatiana; Filho, Silvio; Massie, Shannon; McCrae, Persephone; Johnson, Sarah; Rolian, Campbell; David, Florent (Frontiers in Veterinary Science, 2021)
Background: Swimming is used for rehabilitation and conditioning purposes in equine sports medicine despite the lack of understanding of equine swimming kinematics. The aim of this study was to assess forelimb joints kinematics (elbow, carpus, and fetlock) in swimming horses. The specific objectives were 1- to calculate and compare joint angles in swimming vs. passive mobilizations (PM), 2- to determine joint angular velocities during a swimming stride cycle. Methods: Eleven elite endurance horses swam in a 100-metre straight pool. Underwater (swimming) and overground PM videos were recorded from the horses’ left side. Joint markers were applied on the lateral hoof wall, lateral metacarpal epicondyle, ulnar carpal bone, lateral humeral epicondyle, and the greater tubercle of humerus, from which elbow, carpus and fetlock angles, and angular velocities were obtained. As a reference, maximal fetlock, carpus, and elbow flexion/extension angles were determined during passive mobilization (PM) overground. Differences between angle extrema, angular velocities and range of motion (ROM) were compared statistically. Results: Carpus and fetlock ROM were significantly smaller (p<0.001) during swimming when compared with PM, while there was no difference in elbow ROM between both situations. The carpus had the greatest ROM of all joints during swimming. Absolute angular velocities values of all joints during swimming were greater during retraction than protraction (p<0.001). When compared to other joints during protraction, the carpus joint reached the highest angular velocity. Conclusion: Swimming, as a rehabilitation exercise, has the potential to benefit horses where great elbow ROM with a moderate carpus and fetlock extension are wanted.